O conhecimento no tocante ao autocuidado de homens entregadores por aplicativo durante pandemia da covid-19 - Guerra, Kauana Meire Pereira (2022)
ABSTRACT: Work represents an essential and highly relevant factor for the establishment of relationships and living conditions, especially in contemporary men, where it is established and carried out through it in the world in which they live. The modernity of relationships influences various sectors of daily life, including labor relations, envisioned by the use of digital platforms that manage the workforce of people, mostly men, called uberization of work, which, especially in the Covid Pandemic -19 found in informality a means to support themselves and their families. However, this reality emerged in a work routine of informal workers that may not be known by a large part of the population: the precariousness of work, which brings with it issues inherent to health and that intimately affect the ways of conceiving self-care with health. This type of work is permeated by numerous difficulties, such as long working hours, exposure to inadequate working conditions, inappropriate environments for meals, economic, physical and psychological problems. In this way, the need to carry out studies that cast new perspectives on this population becomes imperative, so that the lived reality is known, so that they are encouraged to change unhealthy behaviors. This study aims to understand, through the speeches of men who work in informal service, specifically, drivers and app delivery people, the knowledge mobilized about self-care in health to maintain their quality of life in times of a pandemic caused by COVID-19. Exploratory study with a qualitative approach, carried out with 10 men who work as delivery people and app drivers and who have their workforce mediated by digital platforms in the municipalities of Cuiabá and Várzea Grande, Mato Grosso. Data collection was carried out through video calls, using semi-structured interviews and a closed questionnaire, with audio recordings being carried out to later be transcribed in full and subjected to thematic content analysis. The results are presented and discussed in the form of two manuscripts: Knowledge and attitudes of workers through apps on self-care in times of the Covid-19 pandemic and Self-care requirements of informal workers during a pandemic in the light of Orem theory. This study allowed for a deeper understanding of the theme, as well as an approximation with the reality faced by informal workers, in particular, delivery people and application drivers. From the reports obtained, the knowledge of the interviewees regarding self-care, self-care attitudes, as well as their implications for health and quality of life, but which is often left in the background, to the detriment of the work performed and of your family's well-being.